Bronchial reactivity and asthma at school age after early-life metapneumovirus infection - Myklebust, Asne (European Respiratory Society, 2026)
Background: The association between early-life lower respiratory tract infection (LRTI) and asthma is well established. Knowledge about bronchial hyperresponsiveness (BHR) and asthma after metapneumovirus (MPV) LRTI is scarce. The aim of this study was to assess BHR and current asthma in school-aged children after hospital admission for early-life LRTI with MPV, and to compare with more well-known viruses, rhinovirus (RV) and respiratory syncytial virus (RSV), and with controls.
Methods: A cohort consisting of children admitted for LRTI and controls was followed-up at school age with a clinical research assessment and lung function tests, including a methacholine provocation test. Current asthma was defined based on objective variable airway obstruction and clinical symptoms. BHR and asthma were compared according to viral groups.
Results: 135 children (median age 9.3 years) were included (16 MPV, 34 RV, 51 RSV, 13 mixed infections and 21 controls). Compared with controls there was increased BHR after MPV and RV LRTI (provocative dose causing a 20% fall in forced expiratory volume in 1 s and dose-response slope; p<0.05). Using Kaplan-Meier statistics, BHR was increased for MPV compared with both controls and RSV (p=0.02 and p=0.01). The proportion of children with current asthma at follow-up was higher in the LRTI children compared with the controls (46% versus 24%; p=0.06). Among children who had undergone MPV and RV infection, 50% fulfilled the asthma criteria compared with 43% in the RSV group (p=0.37).
Conclusion: We found increased BHR and a high prevalence of asthma in school-aged children after early-life MPV infection, and findings were similar to RV, and less to RSV, compared with controls.